(untitled) (Research, Society and Development, 2023)
This study aimed to investigate the effervescence time of vitamin C (ascorbic acid) tablets in water of different hardness. Three brands with a concentration of 1 gram of vitamin C were evaluated in two water samples with a hardness of 71.4 ppm (moderately hard) and 232 ppm (very hard). Two hypotheses were raised about the possible impacts that the hardness of the water would have on the effervescence of the tablets: the first related the pH of the hard water and its influence on the surface tension of the water, and the second related the possibility of the reaction of the ions present in the water with the substances that make up the tablet. The method used to determine total hardness was the MQuant® test, and the two water samples showed hardness of 71.4 and 232 ppm. Then, the disintegration times of the tablets were obtained and compared using the Tukey method. There were no significant differences between the samples analyzed. This work reinforces that additional research is needed on the relationship between water hardness and the effervescence of vitamin C tablets, which helps to understand how the relationship between water quality can affect the use of effervescent medicines.